Effects of supplemental creatine and guanidinoacetic acid on spatial memory and the brain of weaned Yucatan miniature pigs. - Jason L Robinson; Laura E McBreairty; Rebecca A Ryan; Raniru Randunu; Carolyn J Walsh; Gerard M Martin; Janet A Brunton; Robert F Bertolo (PLoS ONE)
The emergence of creatine as a potential cognitive enhancement supplement for humans prompted an investigation as to whether supplemental creatine could enhance spatial memory in young swine. We assessed memory performance and brain concentrations of creatine and its precursor guanidinoacetic acid (GAA) in 14-16-week-old male Yucatan miniature pigs supplemented for 2 weeks with either 200 mg/kg∙d creatine (+Cr; n = 7) or equimolar GAA (157 mg/kg∙d) (+GAA; n = 8) compared to controls (n = 14). Spatial memory tests had pigs explore distinct sets of objects for 5 min. Objects were spatially controlled, and we assessed exploration times of previously viewed objects relative to novel objects in familiar or novel locations. There was no effect of either supplementation on memory performance, but pigs successfully identified novel objects after 10 (p < 0.01) and 20 min (p < 0.01) retention intervals. Moreover, pigs recognized spatial transfers after 65 min (p < 0.05). Regression analyses identified associations between the ability to identify novel objects in memory tests and concentrations of creatine and GAA in cerebellum, and GAA in prefrontal cortex (p < 0.05). The concentration of creatine in brain regions was not influenced by creatine supplementation, but GAA supplementation increased GAA concentration in cerebellum (p < 0.05), and the prefrontal cortex of +GAA pigs had more creatine/g and less GAA/g compared to +Cr pigs (p < 0.05). Creatine kinase activity and maximal reaction velocity were also higher with GAA supplementation in prefrontal cortex (p < 0.05). In conclusion, there appears to be a relationship between memory performance and guanidino compounds in the cerebellum and prefrontal cortex, but the effects were unrelated to dietary supplementation. The cerebellum is identified as a target site for GAA accretion.